Neuroprotective Effects of Curcumin on IL-1β-Induced Neuronal Apoptosis and Depression-Like Behaviors Caused by Chronic Stress in Rats - Fan, Cuiqin (Front Cell Neurosci, 2019)
Depression is suggested to be a neuropsychiatric disease resulting from neuroinflammation within specific brain regions. Curcumin, a potential neuroprotective agent extracted from curcuma loga, exerts antidepressant-like effects in various animal models of depression. However, the underlying mechanisms, in particular whether curcumin may exert neuroprotection through suppression of inflammatory pathway activity in depression remains largely unknown. In the present study, we examined the molecular events of curcumin as related to its capacity for neuroprotection against inflammation-induced neuronal apoptosis and depression-like behaviors in a rat model of depression. Our results show that chronic administration of curcumin (40 mg/kg, i.p., 5 weeks) prior to stress exposure significantly alleviated depression-like behaviors, expression of the proinflammatory cytokine interleukin-1β (IL-1β) and inhibited neuronal apoptosis within neurons of the ventromedial prefrontal cortex (vmPFC). Within the vmPFC of stressed rats, an intracerebral infusion of an RNAi form of IL-1β in adenovirus associated virus (AAV-IL-1β RNAi) significantly ameliorated depression-like behaviors, neuronal apoptosis and reduced phosphorylated-p38 mitogen-activated protein kinase (p-p38 MAPK) expression levels. More important, within the vmPFC of wild type rats, overexpression of IL-1β via intracerebral infusion of AAV-IL-1β induced p38 MAPK phosphorylation and neuronal apoptosis, which could be significantly prevented by chronic treatment of curcumin. Collectively, these findings reveal that curcumin protects against IL-1β-induced neuronal apoptosis, which may be related to the display of depression-like behaviors in stressed rats. Moreover, they provide new insights into the mechanisms and therapeutic potential for curcumin in the treatment of inflammation-related neuronal deterioration in this disorder.